PENGARUH PROFITABILITAS (RETURN ON EQUITY), UKURAN PERUSAHAAN (FIRM SIZE), LEVERAGE (DER), DAN LIKUIDITAS (CR) TERHADAP NILAI PERUSAHAAN (PBV) SEKTOR TRADE, SERVICES, AND INVESTMENT YANG TERDAFTAR DI BEI PADA PERIODE 2014-2018 - Tri Suci Larizki; Krista Novelina; Reka Mawarni Pakpahan; Akbar Reynaldi Hutabarat (JURNAL ILMIAH SOCIO SECRETUM, 2021)
This study aimed at examining and analyzing the effect of Profitability (ROE), Company Size, Leverage (DER), and Liquidity (CR) on the Company Value of trade, service, and investment companies listed in Indonesia Stock Exchange in the 2014-2018 period. The research method used in this study was quantitative research approach. The type of research was descriptive quantitative and explanatory nature of research. The population of this study were one hundred and thirty two (132) trade, service, and investment companies with purposive sampling techniques which obtained the total of twenty (24) trade, service, and investment companies that met the criteria. The method of data analysis in this study was multiple linear regression analysis with classical assumption. The results of this study indicated simultaneously and significantly Profitability (ROE), Company Size, Leverage (DER), and Liquidity (CR) affected the Company Value in of trade, service, and investment sector companies listed in Indonesia Stock Exchange in the 2014-2018 period with the results of Fcount ≥ Ftable 5.713 ≥ 2.45 and significance 0,000 5 0.05. Partially Return On Equity and Current Ratio had significant effect on Firm Value, while Firm Size and Debt To Equity Ratio had no effect and were insignificant to Firm Value. The results of the analysis of the coefficient of determination which obtained adjusted R2 values ​​indicated variations in the Corporate Value variable which could be explained by variations in the Profitability (ROE), Company Size, Leverage (DER), and Liquidity (CR) variables as much as 13.7% while the remaining 86.3% was explained by variations of other variables.